Eight stereoisomers of homonojirimycin from D-mannose. - Lenagh-Snow, G; Jenkinson, S; Newberry, S; Kato, A; Nakagawa, S; Adachi, I; Wormald, M; Yoshihara, A; Morimoto, K; Akimitsu, K; Izumori, K; Fleet, G (2012)
Although there are 32 6-azidoheptitols, there are only 16 homonojirimycin (HNJ) stereoisomers. Two epimeric azidoalditols derived from d-mannose allow the synthesis in water of eight stereoisomers of HNJ.